2010
DOI: 10.1111/j.1477-8947.2010.01298.x
|View full text |Cite
|
Sign up to set email alerts
|

Fast Track Land Reform Programme, tenure security and investments in soil conservation: Micro‐evidence from Mazowe District in Zimbabwe

Abstract: The government of Zimbabwe launched the Fast Track Land Reform Programme (FTLRP) in 2000 as part of its ongoing land reform and resettlement programme which aims to address a racially skewed land distribution. Its goal has been to accelerate both land acquisition and redistribution, targeting at least five million hectares of land for resettlement. This paper investigates the impact of the FTLRP on its beneficiaries' perceptions of land tenure security, and how these subsequently impacted soil conservation inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 32 publications
1
13
0
Order By: Relevance
“…Thus, fear of redistributive measures lowered the importance of land registration in enhancing security of tenure in irrigation systems in Amhara. This finding is similar to that of Moyo () and Zikhali () in rainfed and irrigation farming systems of Zimbabwe where land redistributive measures created some tenure insecurity among smallholders. Yet, in Tigray sites, land redistribution was not viewed as a threat by participants of the study, and indeed interest in land redistribution exists among war returnees and landless youths.…”
Section: Resultssupporting
confidence: 85%
“…Thus, fear of redistributive measures lowered the importance of land registration in enhancing security of tenure in irrigation systems in Amhara. This finding is similar to that of Moyo () and Zikhali () in rainfed and irrigation farming systems of Zimbabwe where land redistributive measures created some tenure insecurity among smallholders. Yet, in Tigray sites, land redistribution was not viewed as a threat by participants of the study, and indeed interest in land redistribution exists among war returnees and landless youths.…”
Section: Resultssupporting
confidence: 85%
“…Tenure security also induces a value‐increasing effect by stimulating forestland investment and enhancing the insurance function of forestland. Studies on farmland tenure have indicated that secure land rights may stimulate farmers to invest in land, thereby raising land values (Brasselle et al , ; Zikhali, ), and in the process create an expectation of a higher rental price (Ma et al , 2015). On the supply side, households have more incentives to rent out land management rights (i.e., use rights) to capture the increased rent resulting from increased tenure security.…”
Section: Conceptual Framework and Propositionsmentioning
confidence: 99%
“…Of the three channels, it is the first that has received the most attention from development scholars. They have analysed how several factors such as political connectivity (Goldstein and Udry, ; Markussen and Tarp, ), inheritance customs (Dillon and Voena, ), migration‐induced population pressures (Grimm and Klasen, ) and land reform programmes (Banerjee et al ., , Holden and Yohannes, ; Deininger and Ali, ; Leight, ; Zikhali, ) influence tenure security and investments.…”
Section: Introductionmentioning
confidence: 99%